Biomimetic nanofibers can construct effective tissue-engineered intervertebral discs for therapeutic implantation. Issue 35 (29th August 2017) - Yang, Junchuan; Yang, Xinglong; Wang, Le; Zhang, Wei; Yu, Wenbo; Wang, Nuoxin; Peng, Baogan; Zheng, Wenfu; Yang, Guang; Jiang, Xingyu
Abstract : We developed a tissue engineered intervertebral disc (TE-IVD) based on biomimetic electrospun PCL/PLGA/Collagen nanofibers to address IVD degradation. Our study provides a novel approach for constructing TE-IVD. Abstract : We present a total tissue engineered (TE) intervertebral disc (IVD) to address IVD degradation, which is a major cause of chronic neck and back pain. The TE IVD is comprised of an alginate hydrogel-based nucleus pulposus (NP) and hierarchically organized, concentric ring-aligned electrospun (ES) polycaprolactone (PCL)/poly (d, l -lactide- co -glycolide) (PLGA)/Collagen type I (PPC)-based annulus fibrosus (AF). The TE IVD exhibits excellent hydrophilicity to simulate highly hydrated native IVD. Long-term in vivo implantation assays demonstrate the excellent structural (shape maintenance, hydration, and integration with surrounding tissues) and functional (mechanical supporting and flexibility) performances of the TE IVD. Our study provides a novel approach for treating IVD degeneration.